Distance Learning-Predictions and Possibilities - John Traxler (MDPI AG, 2018)
Education systems, educational institutions and educational professions, including those of distance learning, can often be inward-looking, backward-looking and self-referential, meaning that they are often fixated on their own concerns, values and processes. In many respects, this is necessary and valuable but the topic of challenges and future trends in distance learning is an opportunity to explore the place of distance learning in a wider world where cultures and ideologies clash, where education and employment are no longer stable and secure, where universities and colleges are under unprecedented pressures, where the technologies and trends of educational technology represent a crowded and chaotic space and where a critical examination of distance learning is necessary to underpin its methods and its mission. This paper addresses in essence three questions, firstly, is the distance learning community clear about the definition and purpose of its work, secondly, what are global political, economic and technological pressures on the institutions of higher education delivering distance learning, and thirdly, what do typical innovations and trends in educational technology signify for distance learning? These are linked questions and the answers constitute challenging predictions and possibilities. The nature of these questions means there are no simple answers only a more complete understanding of a fluid, partial and complex environment within which education, including distance learning, cannot operate in ignorance or isolation.